HUBUNGAN HARGA DAN PROMOSI DENGAN KEPUTUSAN PEMBELIAN KREDIT PEMILIKAN RUMAH (KPR) DI PT BANK MANDIRI JAKARTA KOTA - Mochamad Deden Sukmana, Mas; Hannan, Sufrin; Horas V Purba, Jan (Economicus, 2019)
The purpose of this research is to find out and analyze to find out the relationship of promotion and price together with the purchase decision of KPR at PT Bank Mandiri Tbk Jakarta Kota. This research was carried out at the PT Bank Mandiri Tbk Jakarta Kota office. The results of the study show there is a positive and significant relationship between the price variable and the purchasing decision with the value of the correlation coefficient (r) of 0.769. There is a positive and significant relationship between promotional variables and purchasing decisions with a correlation coefficient (r) of 0.829. There is a positive and significant relationship between price and promotion variables together with purchasing decisions with a correlation coefficient (r) of 0.914. Price contribution (X₁) and promotion (X₂) together towards purchasing decisions (Y) are calculated based on the coefficient of determination or the value of Adjusted R Square (R²) x 100%. Based on the results above, it is known that the Adjusted R Square (R²) = 0.833 value. This shows that 83.3% of purchasing decisions are influenced by price and promotion while the remaining 16.7%, purchase decisions are influenced by other factors which are not discussed in this study.